Total Protein to Creatinine Ratio as an Alternative to Albumin to Creatinine Ratio To Predict Microalbuminuria In Type 2 Diabetes Mellitus - Pokharel, Kabita Khaniya; Pradhan, Santosh; Shrestha, Sweta (Journal of Chitwan Medical College, 2019)
Background: Diabetic nephropathy is the most common complication of diabetes mellitus. Early detection of microalbumin in urine plays an important role in preventing the progression to late stages of chronic kidney disease. For a country like Nepal, the cost of assessment of microalbumin in urine is unaffordable by many patients for regular monitoring. Total protein to creatinine ratio (TPCR) might be a cheaper alternative for this. This study assessed the feasibility of using TPCR as an alternative method for predicting microalbuminuria in diabetic patients.Methods: Type 2 Diabetic patients with age ranging 30-80 years were included in the study after ethical clearance. Urinary total protein was determined by pyrogallol red method and urinary creatinine by Jaffe’s method. Urine for microalbumin was determined by nephelometry. Relationships between variables were examined by Pearson correlation or Spearman’s correlation analysis as appropriate. Receiver operating characteristic (ROC) curve analysis was performed to obtain the cutoff value of TPCR for detection of albuminuriaResults: The mean age of the study population was 55.9 ± 11.8 years. There was significant positive correlation between TPCR and urine albumin (ρ = 0.56; p